Solusi Pemasaran Pada Toko Bu Rani Untuk Meningkatkan Pendapatan Di Desa Kungkai Baru Kabupaten Seluma - Irwanto, Tito; Prayogo, Catur Panggih; Afriani, Sulisti; Putri, Lidya Gustina; Melinda, Tri Febrina (Jurnal Dehasen Mengabdi, 2022)
The purpose of this community service is to assist business actors in promoting SME products in Kungkai Baru Village. This method of community service activities begins with the preparation and field survey stages. This survey phase begins with direct discussions with the Head of Kungkai Baru village, Seluma sub-district, this aims to identify the needs, opportunities, and challenges faced by SME business actors. Then, the socialization and training stages are carried out by the team. At this stage there are five things that the service team does, namely (1) explaining how to make attractive products, (2) finding strategic locations for business actors (3) creating promotional content that is easy for customers to remember (4). And how to distribute the product so that it can reach the customer. (5). Online marketing. The results of this community service activity are as follows: The knowledge of the participants in this case the residents in the Paninggilan Utara Ciledug Village regarding marketing strategies before the PKM activities were mostly in the category of not understanding. After the PKM activity was carried out and the presentation of the material was delivered, it was found that the participants' knowledge of marketing strategies after being delivered was increasing. Keywords : Marketing Strategy,small and medium enterprises.